2019
DOI: 10.20473/jbe.v7i32019.234-241
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Acute Respiratory Infection Cases Before and After Exposure to Volcanic Ash

Abstract: Background: Volcanic ash due to volcanic eruptions has an impact on health. Volcanic ash can cause health problems such as irritation and acute respiratory infections (ARI). Purpose: This study aims to know the outlook of ARI cases before and after exposure to volcanic ash. Methods: This research is a descriptive observational study with a cross-sectional approach that used secondary data from Kepohbaru Health Centre. The population of this study was ARI patients in Kepohbaru Health Centre in February 2013 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…(10). A study shows that the number of ISPA sufferers in men and women is almost the same (11). These results are also supported by research conducted in Sleman which found that there was no significant difference between male ISPA sufferers and female ISPA sufferers.…”
Section: Knowledge Attitudes and Preventive Actions For Ispamentioning
confidence: 65%
“…(10). A study shows that the number of ISPA sufferers in men and women is almost the same (11). These results are also supported by research conducted in Sleman which found that there was no significant difference between male ISPA sufferers and female ISPA sufferers.…”
Section: Knowledge Attitudes and Preventive Actions For Ispamentioning
confidence: 65%